THE REGIME AND THE “REVOLUTION” IN POST-SOVIET GEORGIA - DOLIDZE, Valerian (CENTRAL ASIA AND THE CAUCASUS, 2007)
Three revolutions, one after another, replaced the three post-communist leaders of Georgia:1) the Round Table and Zviad Gamsakhur- dia replaced the communists;2) Gamsakhurdia’s cabinet was replaced by Eduard Shevardnadze, and3) Mikhail Saakashvili removed Shevardnadze from his post. Each of them changed the fortunes of the country and the nation, but only the last event was tagged as a “revolution.” It is obviously viewed as the most important among the three and prompts us to ask whether it is absolutely correct to describe Saakashvili’s coming to power as a revolution. Is it not a ploy designed to boost the importance of the regime change in the eyes of the world community and the local population? To answer these questions we should answer another, broader, question: Did the regime change that removed Eduard Shevardnadze and became known as the Rose Revolution have the characteristics of a revolution? By revolution we mean the very specific and profound impact a regime exerts on social order—t is much more than a conflict that replaces the government. A revolution brings about changes in the political, economic, spiritual, and social spheres of the nation’s life, which take some time to become obvious and are never immediately manifest the very day after forces come to pow-er which choose to call themselves “revolutionary.” The events of November 2003 in Georgia were called a revolution immediately after the coup was completed. During the three years that separate us from that time enough material has been accumulated to assess the nature of the changes that have taken place and were brought about by Mikhail Saakashvili’s coming to pow-er. The Rose Revolution is a term prompted by the immediate impressions of the non-constitutional power change in Georgia. A revolution is not merely a particular method of regime change—it is an event of profound importance for the country’s economic, social, and political